Permeable concrete in roadwork construction / Nurul Natasya Ahmad Sata - Ahmad Sata, Nurul Natasya (2018)
Permeable concrete is a different type of concrete with high porosity that is usually used for roadwork construction and pavement that allows water from heavy rain or other sources to seep through it. Basically, the reason behind the necessary use of permeable concrete is because of the related issues and problems that occur with the use of conventional concrete. There are several problems that occur which are flood incidents, low environment management, road safety and also the negative impact on durability of concrete. The significance of this research is to identify the issues and problems according to the use of conventional concrete, to evaluate the durability and permeability of permeable concrete, and to propose the new concept of permeable concrete that can cope with the stated issues and problems. The methodology used for this research is by critical review of related articles. The used of permeable concrete may reduce the problem of flood incidents where it provides voids to allow water to drain freely and also reduces pollution by lack of environmental management by humans. Besides, with the application of permeable concrete, accidents may be reduced and it may also keep the durability for roadwork construction. Therefore, permeable concrete is a good application for roadwork construction as it can minimize the issues and problems that occurwith the use of conventional concrete.